SnS2 Microsheets for Optical Supramolecular Generation. Issue 6 (11th May 2022) - Zhang, Dan; Lu, Guangliang; Qiu, Yang; Qin, Siqi; Wang, He; Jiang, Jiangang; Zhou, Wenquan; Zhang, Ping; An, Hongchang; Li, Xiaohui
Abstract: Multi‐pulse soliton molecules are observed in passively mode‐locked fiber lasers by using 2D layered metal dichalcogenides (LMDs) as a saturable absorber. LMD has attracted significant attention in photonics and optoelectronics in which tin disulfides (SnS2 ) are implemented for energy storage, photo‐catalysts, and transistor. However, the applications of SnS2 in optoelectronics fields are quite rare. Soliton supramolecules are the self‐assembly of optical solitons into highly‐ordered supramolecular structures which have not been experimentally observed due to the absence of techniques for controlling the inter‐soliton forces. In this article, SnS2 LMDs are successfully applied in a passively mode‐locked fiber laser. It is confirmed that the proposed fiber laser has a center wavelength of 1561.5 nm, a 3‐dB spectral width of 2.45 nm, signal‐to‐noise ratio of 63 dB, and a radiofrequency of 7.2 MHz. The different interiors of the second‐order, third‐order, and ninth‐order bound state of solitons in the cavity are investigated. Furthermore, it is found that numbers of optical solitons self‐assembled into highly ordered supramolecular structures in a passively mode‐locked fiber laser for the first time. The bound state between the six supramolecular soliton units is obtained experimentally and theoretically which have potential applications in ultrafast laser‐field manipulation and optical information storage because of special interactions between pulses. Abstract : SnS2 layered metal dichalcogenides are successfully applied in a passively mode‐locked fiber laser. The bound state between the six supramolecular soliton units is obtained in a passively mode‐locked fiber laser for the first time, which has potential applications in ultrafast laser‐field manipulation and optical information storage because of special interactions between pulses.